Case Report: Trastuzumab Treatment in Adenosquamous Carcinoma of the Extrahepatic Biliary Tract With Her-2 Amplification - Hong, Ye; Li, Xiaofen; Cao, Dan (Frontiers in Oncology, 2021)
Extrahepatic Cholangiocarcinoma (ECC) is an unusual and devastating malignancy which mainly consists of adenocarcinoma. Adeno-squamous carcinoma is a rare histologic type and accounts for 2%-5% of ECC. It was reported 3.6%-8.5% ECC occurred Her-2 amplification. A 45-year old woman was admitted to our hospital because of jaundice. Abdominal computerized tomography (CT) suggested extrahepatic biliary tract cancer. Without surgery contraindication, patient received surgery. Pathological results of surgical specimen verified it was adeno-squamous carcinoma and Fluorescence In Situ Hybridization (FISH) and Next Sequencing Generation technology (NGS) showed tumor had Her-2 amplification. One month after operation, CT demonstrated there was distant lymph node metastasis（pT3N1M1 IV）, patient received gemcitabine and cisplatin combined targeted therapy of trastuzumab and after 3 cycles treatment ,the disease was evaluated partial response ( PR )according to RECIST version 1.1.The progress free survival of 1st line treatment (PFS1) reached to 5 months with5 cycles treatment. After PD then the patient received 3 cycles albumin bound paclitaxel combined S-1 and trastuzumab and concurrent chemoradiotherapy (S-1) because of serious backache. Now, the disease is partial response and PFS of 2nd line treatment (PFS2) has reached to 7 months up to now.